ROLE MODEL (USWAH HASANAH) GURU DALAM PROSES PENDIDIKAN DI SEKOLAH - Septimi Hartati Natalia; Miftahul Jannah; Salami Salami (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
This study explores the vital role of teachers as primary role models, or uswah hasanah, in the process of internalizing moral values ​​in the school environment. The main focus of the study is directed at the influence of educators' personal integrity on the formation of character identity and the overall psychological development of students amidst the dynamics of the modern education ecosystem. This research uses a qualitative approach with a literature review method covering the publication period from 2020 to 2025. The research findings indicate that teachers function as behavioral reference centers through students' natural imitation mechanisms, with concrete exemplary manifestations that include aspects of religiosity, time discipline, democratic communication, and social concern. The success of this character transformation depends heavily on the consistency of program implementation and the synergy of cooperation between schools and parents. Despite several obstacles such as a lack of creative methods and interference from the external environment, educator integrity remains proven to be a far more effective pedagogical instrument than mere theoretical verbal instruction. The main conclusion emphasizes that optimizing the role of teachers as true role models is a fundamental key in building the ethical foundation of the next generation with noble morals. Educators are not only tasked with transferring knowledge, but also building souls through the power of consistent concrete actions to create a dignified and superior quality of national civilization for the sustainable and holistic advancement of Indonesian society. ABSTRAK Penelitian ini mengeksplorasi peran vital guru sebagai figur teladan utama atau uswah hasanah dalam proses internalisasi nilai moral di lingkungan sekolah. Fokus utama kajian diarahkan pada pengaruh integritas personal pendidik terhadap pembentukan identitas karakter serta perkembangan psikologis siswa secara menyeluruh di tengah dinamika ekosistem pendidikan modern. Riset ini menggunakan pendekatan kualitatif dengan metode studi literatur yang mencakup periode publikasi dari tahun 2020 hingga 2025. Temuan penelitian menunjukkan bahwa guru berfungsi sebagai pusat referensi perilaku melalui mekanisme imitasi alami siswa, dengan manifestasi keteladanan konkret yang meliputi aspek religiusitas, kedisiplinan waktu, komunikasi demokratis, serta kepedulian sosial. Keberhasilan transformasi karakter ini sangat bergantung pada konsistensi implementasi program serta sinergi kerja sama antara pihak sekolah dengan orang tua. Meskipun terdapat beberapa hambatan seperti kurangnya kreativitas metode dan gangguan dari lingkungan eksternal, integritas pendidik tetap terbukti menjadi instrumen pedagogis yang jauh lebih efektif dibandingkan sekadar instruksi verbal teoritis. Simpulan utama menegaskan bahwa optimalisasi peran guru sebagai role model sejati merupakan kunci fundamental dalam membangun fondasi etika generasi penerus yang berakhlak mulia. Pendidik tidak hanya bertugas mentransfer ilmu pengetahuan, melainkan juga membangun jiwa melalui kekuatan tindakan nyata yang konsisten guna menciptakan kualitas peradaban bangsa yang bermartabat serta unggul bagi kemajuan masyarakat Indonesia secara berkelanjutan dan holistik.